Leaves of grass : the sesquicentennial essays - Belasco, Susan, 1950-; Folsom, Ed, 1947-; Price, Kenneth M. (University of Nebraska Press, 2007)
Contains seventeen essays by pre-eminent scholars representing a variety of critical perspectives that focus on Walt Whitman's "Leaves of Grass". This book features contributors who treat Whitman's poetry, his biography, his politics, his reception in the United States and abroad, race and ethnic issues, and nineteenth-century America